2016
DOI: 10.5817/soc2016-2-55
|View full text |Cite
|
Sign up to set email alerts
|

The Village of the Year Competition Constructing an Ideal Model of a Rural Community in Finland

Abstract: The Village Action Association of Finland (SYTY) organizes the Village of the Year competition annually to award active rural communities. The competition has taken place since 1985, but after the village action movement was integrated into Finnish rural policy networks in the 1990s, it also became a part of rural policy instruments. The competition can be considered a governing technique that constructs norms and an ideal model for rural communities to pursue. In this article, I study the representation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Development‐oriented rural communities can be regarded as an example of neoliberal governing where responsibilities are transferred to individual citizens and local communities (Rose ; Marinetto ; Kumpulainen ). In Finland, the rationality of community development has been widely adopted as the norm to ‘save’ the villages in rural areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Development‐oriented rural communities can be regarded as an example of neoliberal governing where responsibilities are transferred to individual citizens and local communities (Rose ; Marinetto ; Kumpulainen ). In Finland, the rationality of community development has been widely adopted as the norm to ‘save’ the villages in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The rural communities in the study have received awards for their work in the provincial Village of the Year competition (in the years 2005, 2006, 2007), which means that they have been recognised as active community developers. These villages can be considered to represent ideal rural communities, setting an example for how to promote local development practices (Kumpulainen ) but also serving as ‘policy laboratories’ – places to study the effects of rural policy objectives compared to the majority of Finnish villages, as these ‘policy laboratories’ are more actively adopting community development practices as instruments to promote local development.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2015 study on village competitions in the Czech Republic (Pospech et al 2015) found that the national village of the year contest favoured representations and images of 'the good village' centred around everyday life and social activities of the inhabitants and thus produced a specific type of rural idyll (p. 68). A study from Finland (Kumpulainen, 2016) reviewed the criteria for a national village of the year competition in which strategic planning, development projects, self-responsibility for local welfare, and a focus on cultural heritage and community spirit were core elements in line with the neoliberal approach. Kumpulainen found that the community's internal factors had become the key to success or the cause of decline (p. 61) and concluded by saying that the 'competition can be considered a governing technique that constructs norms and an ideal for rural communities to pursue' (p. 55).…”
Section: Introductionmentioning
confidence: 99%